How Firms in Turbulent Environments Measure Strategic Performance - Barrows, Edward (Cranfield University, 2014)
This thesis presents the findings from two case study examinations of strategic performance measurement systems within two turbulent environmental contexts: the U.S. security software industry and the U.S. health care industry. Despite a three-‐decade emphasis on performance measurement research, little empirical work has been carried out inside turbulent settings—contexts characterized by rapid change, high levels of instability and complex configurations among environmental variables. This research targets that gap. Through exploratory case studies from seven security software firms paired with a single in-‐ depth case investigation within a transforming health care system, this study addresses the question: “how do firms in turbulent environments measure strategic performance?” The research found that in turbulent environments, an effective strategic performance measurement system contains six interrelated elements: management aims, performance objectives, uncertainty areas, decision data, management attention and performance measures. Top managers focus on their aims and performance objectives to meet requirements via a closed-‐loop approach while monitoring uncertainty areas and gathering decision data in an open-‐loop way. This union of feedback and feedforward control enables dynamic interaction among the various elements of the system all of which are informed by performance measure data. Effective use is moderated by management’s focus of attention. The research has implications for information processing and management control literature; it extends existing theory to incorporate the use of semi-‐structures within the framework of the strategic performance measurement system as a means of overcoming the challenges of uncertainty. Further, the research contradicts both extant literature and practice convention that claims strategic performance measurement frameworks need to be balanced to be effective. Practitioners are provided with a strategic performance measurement framework for use in turbulent environments. The framework would benefit from further examination in a variety of different, equally turbulent, contexts.
Keywords: cybernetics; information processing; management attention; management control; strategic control; strategic performance measurement